Exploring the Malaysian Chinese business: A review - Ku Hasnan, Ku Halim; Mohd. Ainuddin Iskandar Lee, Abdullah; Zahrul Akmal, Haji Damin; Yusri, Yusof; Jamal Rizal, Razali; Mohd Mizan, Mohammad Aslam (Universiti Malaysia Pahang, 2024)
The paper will explore the momentum of the Chinese business in Malaysia into a consistent and competitive performance thereby making it possible to continue to lead the domestic business environment despite the many challenges before and after independence of Malaya. This paper employed the historical views conducted through literature content analysis. As a result, the study discovered that the business strategy used, particularly the maneuver capability factors in Chinese-owned companies before and after independence. Business maneuver methods were common strategies applied by the Chinese enterprises to increase the number of firm size during the period of the implementation of NEP era. The companies responded to the government’s call in opening up the ownership of shares for the Malay-Bumiputera investors without affecting their performance. Innovation to the preservation of Chinese-owned businesses in the era of NEP indicates that the companies practiced a partnership especially the small and medium enterprises and family businesses. Overall, it has proved that the dynamics of the company's business in the Chinese business based on the concept of maneuver allowed Chinese owned companies not only to survive, but to compete successfully and expand tremendously during the NEP era.